From EU expansion to Brexit: Free movement and the UK from 2004 to 2021 - Portes, Jonathan (Border Crossing, 2025)
I examine the impact of free movement within the European Union on the UK after the decision to allow immediate access to the labour market for workers from the new Member States which joined the EU in 2004. This – and the subsequent accession of Bulgaria and Romania – led to large migration flows to the UK, with both economic and political consequences. Since the Brexit referendum, these flows have largely ceased, but the legacy of this period is a very large and now well-established group of EU-origin migrants, most of whom will ultimately acquire UK citizenship.